A note on the problem of finding a (3,9)-cage - P. K. Wong (International Journal of Mathematics and Mathematical Sciences)
In this paper, we discuss The poblem of finding a (3,9)-cage. A hamiltonian graph with girth 9 and 54 vertices is given. Except four vertices, each of the remaining vertices of this graph has valency Three. This graph is obtained with the aid of a computer.